Combination of mitochondria targeting doxorubicin with Bcl-2 function-converting peptide NuBCP-9 for synergistic breast cancer metastasis inhibition. Issue 5 (14th January 2021) - Yang, Jiatao; Li, Qiuyi; Zhou, Rui; Zhou, Minglu; Lin, Xi; Xiang, Yucheng; Xie, Dandan; Huang, Yuan; Zhou, Zhou
Abstract : Distant organ metastasis is the main cause of death in breast cancer patients. Abstract : Distant organ metastasis is the main cause of death in breast cancer patients. Evidences have shown that mitochondria also play a crucial role in tumor metastasis, except for as apoptosis center. However, the treatment of tumor growth and metastasis was reported to be limited by mitochondria-associated protein Bcl-2, which are gatekeepers of apoptosis and are found to reside in mitochondria mainly. Herein, we designed a mitochondria-targeting doxorubicin delivery system as well as a mitochondrial distributed Bcl-2 function-converting peptide NuBCP-9 delivery system, which are both based on N -(2-hydroxypropyl)methacrylamide copolymers, to achieve a synergistic effect on tumor regression and metastasis inhibition by combination therapy. After mitochondria were damaged by mitochondria-targeting peptide-modified doxorubicin, apoptosis was effectively enhanced by mitochondrial specifically distributed NuBCP-9 peptides, which converted Bcl-2 function from anti-apoptotic to pro-apoptotic and paved the way for the development of mitochondrial impairment. The combination treatment exhibited significant damage to mitochondria, including excess reactive oxygen species (ROS), the permeabilization of mitochondrial outer membrane (MOMP), and apoptosis initiation on 4T1 breast cancer cells. Meanwhile, besides enhanced tumor growth suppression, the combination treatment also improved the inhibition of 4T1 breast cancer metastasis both in vitro and in vivo . By increasing the expression of cytochrome C and decreasing the expression of Bcl-2, metal matrix protease-9 (MMP-9) as well as vascular endothelial growth factor (VEGF), the combination treatment successfully decreased 84% lung metastasis. Overall, our work provided a promising strategy for metastatic cancer treatment through mitochondria-targeting anti-cancer drug delivery and combination with mitochondrial distributed Bcl-2 function-converting peptide.